ИСПЫТАНИЕ ИММОБИЛИЗОВАННЫХ НА МИНЕРАЛЬНЫЕ СОРБЕНТЫ МИКРООРГАНИЗМОВ-НЕФТЕДЕСТРУКТОРОВ В АРИДНЫХ УСЛОВИЯХ МАНГИСТАУСКОЙ ОБЛАСТИ (Experimental biology, 2009)
The present paper presents the results of studies on the oxidizing activity of free and immobilized cells on mineral sorbents microorganisms oil destructors conducted under field conditions at Karazhanbas Mangistau region. The greatest oil destructor activity was observed in oil destructor microorganisms immobilized on a concrete block.
Keywords: mineral sorbents; Karazhanbas Mangistau region